Use of selected scavengers for the determination of NF-TiO2 reactive oxygen species during the degradation of microcystin-LR under visible light irradiation - Pelaez, M.; P. Falaras; V. Likodimos; O'Shea, K.; de la Cruz, A.A.; Dunlop, P.S.M.; Byrne, J.A.; Dionysiou, D.D. (Journal of Molecular Catalysis A: Chemical, 2016)
Although UV-induced TiO2 photocatalysis involves the generation of several reactive oxygen species (ROS), the formation of hydroxyl radicals is generally associated with the degradation of persistent organic contaminants in water. In this study, a variety of radical scavengers were employed to discriminate the roles of different ROS during visible light-activated (VLA) photocatalysis using nitrogen and fluorine doped TiO2 (NF-TiO2) in the degradation of the hepatotoxin, microcystin-LR (MC-LR) in water. The addition of hydroxyl radical scavengers, methanol and tert-butyl alcohol to the reaction mixture resulted in negligible inhibition of NF-TiO2 photocatalytic degradation of MC-LR at pH 3.0 and only partial inhibition at pH 5.7 under visible light. While hydroxyl radicals ([rad]OH) generally play the primary role in UV-TiO2 photocatalysis, the minimal influence of MeOH and t-BuOH on the degradation process under these experimental conditions indicates that [rad]OH are not crucial in VLA NF-TiO2 photocatalysis. However, strong inhibition was observed in VLA NF-TiO2 photocatalytic degradation of MC-LR in the presence of superoxide dismutase, benzoquinone and catalase at pH 3.0 and 5.7 indicating that O2[rad]− and H2O2 play critical roles in the degradation process. Similar degradation rates were observed in the presence of deuterium oxide, which enhances singlet oxygen mediated processes further suggesting singlet oxygen is not a key species in the degradation of MC-LR. Formic acid and cupric nitrate were added to probe the roles of the valence band holes and conduction band electrons, respectively. Under UV–vis light irradiation, almost complete inhibition of MC-LR removal is observed with NF-TiO2 in the presence of [rad]OH scavengers at pH 5.7. These results demonstrate that the solution pH plays a major role in the formation and reactivity of ROS during VLA NF-TiO2 photocatalysis. The adsorption strength of scavengers and MC-LR onto NF-TiO2 as well as the speciation of ROS as a function of pH needs to be carefully considered since they also play a major role in the efficiency of the process. These results indicate that the reduction of molecular oxygen by photo-generated electrons rather than hydroxyl radicals produced by oxidative reactions of photo-generated holes is the key factor in the VLA NF-TiO2 photocatalytic degradation of MC-LR. © 2016 Elsevier B.V.
cited By 77